Pelatihan Pembuatan Lemang dengan Menggunakan Daun Pandan untuk Memperpanjang Umur Simpan Lemang Sebagai Oleh-oleh Desa Tanjung Sirih Kabupaten Lahat - Melati Pratama (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The problem of Lemang Tanjung Sirih Lahat Regency producers to sell Lemang as souvenirs was the shelf life of Lemang that just one day in room temperatrue. Therefore, the objective of this research was to train Lemang producers for produce Lemang using pandan leave to get Lemang in longer shelf life, so it can be souvenir of Lahat district. The training used three methods such as counseling, technical guidance, and evaluation. The counseling was conducted for one day in The Grands of Lahat District hotel, while techincal guidance and evaluation in Tanjung Sirih village hall for three days. The counseling was followed 70 peoples of Lemang producers, while technical guidance was followed 35 peoples of Lemang producers. The content of counseling include the characteristics of Lemang and product development for increase the added value and competitivenes of Lemang. The content of technical guidance include the characteristic of pandan leaves and Lemang production. The conclution from evalution between participants, organizers, and sources was necessity of periodic training.